Comparison of maximal oxygen uptake and ventilatory threshold during skating, running and cycling exercise in ice hockey players - duManoir, G. R.; Cheveldayoff, K. B.; Zayac, M.; Bamford, J. A.; Loitz, C. C.; Bell, G. B. (Advances in Exercise and Sports Physiology, 2005)
The primary purpose of this investigation was to compare different modes of testing ventilatory threshold and maximal oxygen uptake in ice hockey players. Eleven male hockey players completed continuous graded exercise protocols to volitional exhaustion on a cycle ergometer, a running treadmill, and on a skating treadmill. The skating treadmill protocol was also repeated on different days to determine reliability of this latter device. Ventilatory threshold was significantly higher during running treadmill exercise compared to all other modes, and significantly higher using the skating treadmill compared to the cycle ergometer. Maximal ventilation was significantly higher during exercise on the cycle ergometer than the other exercise modes, and significantly higher using the skating treadmill compared to the running treadmill. There were no significant differences in maximal oxygen uptake, tidal volume, respiratory frequency or heart rate responses between any exercise test mode during maximal exercise. There was no significant difference for any maximal physiological variable between the three skating treadmill trials. These findings suggest that testing maximal oxygen uptake can be validly and reliably assessed using a skating treadmill. However, ventilatory threshold may be lower than achieved on the running treadmill but higher than during cycle ergometer in ice hockey players.